A Study of Techniques and Management of Inventory - Kumar, Sanjeev (Journal of Commerce and Trade, 2011)
Inventory management is an integral part of a successful business. Inventories typically consist of goods, raw materials and finished products. Each of these elements translates into money for the business owner. The key to profitability is a carefully balanced inventory. Balanced inventories are important because many businesses rely on its stock of items to make a profit. Stockpiles that never move from the shelves do little good for the company. A proper balance is of the utmost importance. At the same time, there are issues with inventory control when there isn’t enough stock on hand. One common problem is running out of inventory, which is caused by trying to reduce inventory costs too much. This is something that no business wants to have happen, but it happens to virtually all of them at some point. Even the largest stores run out of certain products from time to time when they sell or use more than they expected. This can cause financial losses when inventory is not available for customers to purchase. Part of inventory control is trying to minimize shortages so these are rare occurrences. Most businesses expect they will have shortages on occasion and they have calculated that the small loss is worth the money saved by not having an overstock.